2012
DOI: 10.1039/c1cc15926g
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional peptides that precisely biomineralize Au clusters and specifically stain cell nuclei

Abstract: A bifunctional peptide containing a domain that targets cell nuclei and a domain with the ability to biomineralize and capture Au clusters is presented. The peptide-Au clusters exhibit red emission (λ(em) = 677 nm) and specifically stain the nuclei of three cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
121
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 30 publications
8
121
0
1
Order By: Relevance
“…Studies on peptides showed that the coexistence of cysteine and tyrosine in peptides can determine if a biomolecule can potentially mediate the formation of photoluminescent, red-emitting gold clusters. These observations provide experimental evidence for earlier assumptions [3,14]. Furthermore, our results showed that effectiveness of cysteine residues is not hindered by their disulfide-bonded state.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Studies on peptides showed that the coexistence of cysteine and tyrosine in peptides can determine if a biomolecule can potentially mediate the formation of photoluminescent, red-emitting gold clusters. These observations provide experimental evidence for earlier assumptions [3,14]. Furthermore, our results showed that effectiveness of cysteine residues is not hindered by their disulfide-bonded state.…”
Section: Discussionsupporting
confidence: 76%
“…We observed the same effect when tyrosine was replaced by tryptophan. These results revealed that cysteine and tyrosine are exclusively responsible for cluster formation and cannot be substituted by other residues, which is an experimental evidence for earlier assumptions [3,14]. Cysteine might be essential in cluster formation due to the electron withdrawing effect of the thiol-gold bond, which plays a crucial role in cluster stabilization [44].…”
Section: Preparation Of Auqcs With Peptidessupporting
confidence: 57%
See 2 more Smart Citations
“…The quantum efficiency was determined to be ∼12.3% (Fig. S3), which was similar to those reported for peptide-templated AuNCs (Gu et al, 2014;Wang et al, 2012). The transmission electron microscope (TEM) was used to directly observe the morphology of the peptide-AuNCs.…”
Section: Characterization Of Peptide-auncsmentioning
confidence: 98%